GIS for dummies - DeMers, Michael N. (Hoboken, NJ : Wiley, 2009)
Examines the diverse applications of geographic information systems, with explanations of how GIS technology captures, stores, counts, characterizes, integrates, analyzes, and displays data, and a discussion of spatial and mapping concepts, GIS system components, and how to design, implement, and navigate a GIS system.
GIS : geography on steroids: Seeing the scope of GIS ; Recognizing how maps show information ; Reading, analyzing, and interpreting maps -- Geography goes digital: Creating a conceptual model ; Understanding the GIS data models ; Keeping track of data descriptions ; Managing multiple maps ; Gathering and digitizing geographic data -- Retrieving, counting, and characterizing geography: Finding information in raster systems ; Finding features in vector systems ; Searching for geographic objects, distributions, and groups -- Analyzing geographic patterns: Measuring distance ; Working with statistical surfaces ; Exploring topographical surfaces ; Working with networks ; Comparing multiple maps ; Map algebra and model building -- GIS output and application: Producing cartographic output ; Generating non-cartographic output ; GIS in organizations -- The part of tens: Ten GIS software vendors ; Ten questions to ask potential vendors ; Ten GIS data sources.
Includes index.
Keywords: Geographic information systems